Mapping destination competitiveness in Indonesia’s Nusa Tenggara Timur (NTT) province: A Malmquist–data envelopment analysis approach - Bire, Rio Benedicto (Regional science policy & practice, 2021)
This research explores destination competitiveness in the Nusa Tenggara Timur (NTT) Province of Indonesia. Absence of empirical studies related to destination efficiency in Indonesia, and the significant uprise of the tourism sector in NTT, justify the study. We employed a Malmquist–data envelopment analysis (DEA) to assess performances of regions in NTT. Results presented technical efficiency and efficiency change indexes, and further provisions regarding managerial implications. Regional tourism stakeholders therefore should adhere to the new scenario, which may entail radical rethinking regarding their traditional ways of defining, structuring, and distributing tourism products. Resumen Esta investigación explora la competitividad de los destinos en la provincia indonesia de Nusa Tenggara Timur (NTT). La ausencia de estudios empíricos relacionados con la eficiencia de los destinos en Indonesia, y el importante auge del sector turístico en NTT, justifican el estudio. Se empleó un análisis envolvente de datos de Malmquist (DEA, por sus siglas en inglés) para evaluar el desempeño de las regiones en NTT. Los resultados presentaron los índices de eficiencia técnica y los de cambio de eficiencia, así como otras disposiciones relativas a las implicaciones para la gestión. Los agentes turísticos regionales deben adherirse por tanto al nuevo escenario, lo que puede significar un replanteamiento radical de sus formas tradicionales de definir, estructurar y distribuir los productos turísticos. 抄録 本研究は、インドネシアのヌサトゥンガラティムール (NTT)州における観光地としての競争力を調査する。インドネシアにおける観光地の性能に関連した実証研究が欠如しており、NTTにおける観光セクターが著しく勃興していることが、研究を行う根拠である。マルムキスト指標を用いたデータ包絡分析法 (data envelopment analysis: DEA)を用いて、NTT州の地域の動向を評価した。結果から、技術的な性能と性能の変化の指標、および経営への影響に関する対策が示された。したがって、地域の観光業の利害関係者は、観光商品を定義し、構造化し、流通させる従来の方法について抜本的に再考する必要性にせまられる可能性があるが、新しいシナリオに従うべきである。